2016
DOI: 10.1371/journal.pone.0160526
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ethnicity on the Accuracy of Non-Invasive Scores Predicting Non-Alcoholic Fatty Liver Disease

Abstract: ObjectivesPresence of non-alcoholic fatty liver disease (NAFLD) can predict risks for diabetes, cardiovascular disease and advanced liver disease in the general population. We aimed to establish a non-invasive score for prediction of NAFLD in Han Chinese, the largest ethnic group in the world, and detect whether ethnicity influences the accuracy of such a score.MethodsLiver fat content (LFAT) was measured by quantitative ultrasound in 3548 subjects in the Shanghai Changfeng Community and a Chinese score was cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
0
20
1
Order By: Relevance
“…However, the performance of HSI in our pilot study was weaker as compared with AUROC 0.812 [0.801; 0.824] described by Lee et al . There are many factors that might contribute to different diagnostic efficacy of the indices, among them—ethnicity, morbidities, and method for diagnosis of liver steatosis being the main . All 40 patients in our study were white Europeans with type 1 diabetes and without previously diagnosed liver diseases.…”
Section: Discussioncontrasting
confidence: 66%
“…However, the performance of HSI in our pilot study was weaker as compared with AUROC 0.812 [0.801; 0.824] described by Lee et al . There are many factors that might contribute to different diagnostic efficacy of the indices, among them—ethnicity, morbidities, and method for diagnosis of liver steatosis being the main . All 40 patients in our study were white Europeans with type 1 diabetes and without previously diagnosed liver diseases.…”
Section: Discussioncontrasting
confidence: 66%
“…This potentially could have led to diagnostic misclassification. Validation studies of the FLI in other Chinese populations have reported areas under the receiver operating curve (AUROC) ranging from 0.76 to 0.88, but given that we used a higher FLI cut‐off value than that recommended for the Chinese population, we expect to have smaller misclassification bias. Furthermore, because our study population is relatively ethnically homogeneous (Han Chinese), we anticipate a higher AUROC of the FLI in this analysis.…”
Section: Discussionmentioning
confidence: 98%
“…[137][138][139] Thus, caution is requested when extrapolating results of noninvasive tests from nondiabetic populations to patients with diabetes. Also the role of ethnicity may be important to take into account, 140,141 as most available studies have been done in Caucasians. Further studies are needed to address these issues.…”
Section: Special Populations and Controversiesmentioning
confidence: 99%